Myosin-actin interaction plays an important role in human immunodeficiency virus type 1 release from host cells. - Sasaki, H (1995)
We examined the potential role of myosin and actin in the release of human immunodeficiency virus type 1 (HIV-1) from infected cells. Wortmannin (100 nM to 5 microM), an effective inhibitor of myosin light chain kinase, blocked the release of HIV-1 from infected T-lymphoblastoid and monocytoid cells in a concentration-dependent manner. Cytochalasin D, a reagent that disrupts the equilibrium between monomeric and polymeric actin, also partially inhibited the release of HIV-1 from the infected cells. At the budding stage, myosin and HIV-1 protein were detected in the same areas on the plasma membrane by using dual-label immunofluorescence microscopy and immunoelectron microscopy. In the presence of 5 microM wortmannin, viral components were observed on the plasma membrane by using immunofluorescence microscopy and electron microscopy, implying that wortmannin did not disturb the transport of viral proteins to the plasma membrane but rather inhibited budding.